Diagnostic value of computed tomography colonography (CTC) after incomplete optical colonoscopy. (September 2016) - Maggialetti, N.; Capasso, R.; Pinto, D.; Carbone, M.; Laporta, A.; Schipani, S.; Piccolo, C.L.; Zappia, M.; Reginelli, A.; D'Innocenzo, M.; Brunese, L.
Abstract: Introduction: This study evaluated the role of computed tomography colonography (CTC) in patients who previously underwent incomplete optical colonoscopy (OC). We analyzed the impact of colonic lesions in intestinal segments not studied by OC and extracolonic findings in these patients. Methods: Between January 2014 and May 2015, 61 patients with a history of abdominal pain and incomplete OC examination were studied by CTC. CTCs were performed by 320-row CT scan in both the supine and the prone position, without intravenous administration of contrast medium. In all patients both colonic findings and extracolonic findings were evaluated. Results: Among the study group, 24 CTC examinations were negative for both colonic and extracolonic findings while 6 examinations revealed the presence of both colonic and extracolonic findings. In 24 patients CTC depicted colonic anomalies without extracolonic ones, while in 7 patients it showed extracolonic findings without colonic ones. Discussion: CTC is a noninvasive imaging technique with the advantages of high diagnostic performance, rapid data acquisition, minimal patient discomfort, lack of need for sedation, and virtually no recovery time. CTC accurately allows the evaluation of the nonvisualized part of the colon after incomplete OC and has the distinct advantage to detect clinically important extracolonic findings in patients with incomplete OC potentially explaining the patient's symptoms and conditioning their therapeutic management. Conclusion: CTC accurately allows the assessment of both colonic and extracolonic pathologies representing a useful diagnostic tool in patients for whom complete OC is not achievable. Highlights: We used computed tomography colonography (CTC) after incomplete optical colonoscopy. CTC was useful to detect both colonic and extracolonic otherwise overlooked findings. CTC is the recommended examination in first line colorectal cancer evaluation.